Integrating Scrabble Online as a Tool To Support for Vocabulary Learning - Ayumi Pratiwy Tanjung; Rahmah Fithriani (Scope : Journal of English Language Teaching, 2023)
Scrabble online is an application that can be used to teach vocabulary. In this particular study, researchers used online scrabble on students from a high school in Simalungun. There were six participants in this study. The purpose of this study is to find out how students feel about the effectiveness of using online scrabble to improve their vocabulary. The question that needs to be answered in this study is, "How do students perceive the use of online scrabble in learning vocabulary?" The study presented here was a qualitative descriptive study. Data collected through interviews were then transcribed verbatim and analyzed using content analysis. As a result of this study, it can be concluded that scrabble online is an application that can help students improve their vocabulary when learning English.